Pengembangan Majalah Digital Berbantu Canva Meningkatkan Literasi Sains Siswa SMP - Tutut Tutut Pratiwi Pratiwi (JURNAL SPEKTRA, 2022)
This research produced a canvas-assisted digital physics magazine with material on frequency, waves and sound and their application in daily life. This study used the ADDIE model, namely analysis design development implementation and evaluation. In this study, it was only carried out at the development stage. This research was conducted at SMP Negeri 34 Purworejo with the subject of a limited trial of 5 students and an extensive test of 31 students. The instrument used in this study was a validation sheet, a lesson plan implementation sheet, a note sheet on the constraints of a scientific literacy skill test and student response questionnaires.based on the results of the study, the results obtained (1) validation of digital physics magazines assisted by Canva is valid (2) the implementation of RPP gets an average score of 3.72 and reliability is 99% and (3) the results of the scientific literacy ability test get results of 0.63 in the medium category , the Wilcoxon test got 0.000 which means that there was an effect of learning using digital physics magazines assisted by Canva, student response questionnaires with a percentage of 82% in the good category.